Socioeconomic inequalities in adolescent health complaints: A multilevel latent class analysis in 45 countries - Hammami, Nour; Gobina, Inese; Lukoševičiūtė, Justė; Kostičová, Michaela; Lyyra, Nelli; Gariepy, Genevieve; Šmigelskas, Kastytis; Baban, Adriana; Malinowska-Cieślik, Marta; Elgar, Frank J. (Current Psychology, 2023)
Our study evaluated the relationship between adolescent health complaints and socioeconomic position in 45 countries. Data are from the 2017/2018 international Health Behaviour in School-aged Children survey which used proportionate sampling among adolescents aged 11 to 15 years old (n=228,979). Multilevel, multinomial regression analysis assessed the association between the multilevel latent classes with socioeconomic status (SES; at the household and country level). Three distinct latent classes were identified: No Complaints, Psychological Complaints, and a Physical and Psychological Complaints class; where, low household SES was highest for the physical and psychological complaints class. The findings suggest that health promotion policies and interventions among adolescents should consider the specific needs of adolescents living with low household SES as they report more subjective health complaints.
Keywords: Adolescents; HBSC; Mental health; Multiple health complaints; Psychosomatic; Socioeconomic position